Retrospective study of 59 cases of cancer-associated thrombotic microangiopathy: presentation and treatment characteristics. Issue 4 (6th July 2022) - Decaestecker, Antoine; Hamroun, Aghilès; Provot, François; Rondeau, Eric; Faguer, Stanislas; Sallee, Marion; Titeca-Beauport, Dimitri; Rebibou, Jean Michel; Forestier, Alexandra; Azar, Raymond; Deltombe, Clément; Wynckel, Alain; et al.
ABSTRACT: Background: Cancer-associated thrombotic microangiopathy (TMA) is a rare disease, with a poor prognosis. The classical treatment is urgent chemotherapy. Few data are available on the efficacy of plasma exchange (PE) and eculizumab in these patients. Methods: Cases of cancer-related TMA treated between January 2008 and December 2019 in 12 French treatment centres were retrospectively analysed, excluding cases associated with chemotherapy and stem cell transplantation. Patients were divided into four groups depending on the treatment received: none, PE therapy alone, chemotherapy, with or without PE therapy, or eculizumab, with or without chemotherapy and PE therapy. Results: The data of 59 patients with cancer-associated TMA were analysed. Twenty of these cases were related to a cancer recurrence. The cancer was metastatic in 90% of cases (53/59). Bone marrow invasion was observed in 20/41 biopsies. Some laboratory results, including disseminated intravascular coagulation high ferritin and C-reactive protein, were suggestive of cancer. None of the 16 patients whose alternative complement pathway was assessed had abnormal levels of protein expression or activity. The median survival time was 27 days. Chemotherapy was significantly associated with improved survival, with a 30-day survival rate of 85% (17/20) among patients who received PE and chemotherapy, versus 20% (3/15) among patients who received PE alone. Patients treated with eculizumab in addition to chemotherapy and PE therapy did not have longer overall survival or higher haematological remission rates than those treated with chemotherapy and PE therapy alone. Renal remission rates were non-significantly higher, and times to remission non-significantly shorter, in the eculizumab group. Conclusions: Nephrologists and oncologists should make themselves aware of cancer diagnoses in patients with TMA and bone marrow biopsies should be performed systematically in these cases. All 59 patients had poor survival outcomes, but patients treated with urgent initiation of chemotherapy survived significantly longer than those who were not. Graphical Abstract: